Efeitos da sucralose no rim fetal de ratos: estudo morfométrico - Rodero, Ademir Barianni (2010)
The increase of overweight people has amplified the risks for diseases like diabetes mellitus, systemic hypertension and endometrial cancer, breast or intestine. In searching for alternatives to lose weight, consumption of sweeteners has proved worrisome because of their indiscriminate use, especially in diabetics and women of reproductive age. Sucralose is a sweetener discovered recently, derived from the chlorination of sucrose to 3 hydroxyl radicals. Justificative: Experimental studies with sucralose and its hydrolysis products, through various routes of administration and doses, showed clinical and histopathological changes in the digestive, immune and nervous systems, as well as in spleen and adrenal glands, and proven maternal and fetal toxicity. Objective: To determine the histological changes induced by sucralose in the kidney of fetuses during pregnancy, as well as morphological effects on fetal and placental weights and the length of the umbilical cord. Material and Methods: Sucralose was administered by gavage (30 mg/kg to weight / day), from the 10th up to the 14th day of pregnancy in five rats (treated group), and the same volume of saline solution in five rats by the same route (control group). On the twentieth day of pregnancy, all animals were sacrificed and weighed, with removal of the fetal kidneys and analysis of the fetal weight, placenta weight and umbilical cord length. They were evaluated the volume of glomeruli and morphometry of the nuclei of cells of proximal and distal convoluted tubules and collecting duct, determining the major, minor and mean diameter; ratio between major diameter and minor diameter, perimeter, volume, area, relation volume/area; eccentricity, coefficient of form and index of contour. Results: The fetal weight and length of the umbilical cord of the treated group were significantly lower in the control group (value: p<0.01), although not statistically significant compared to the weight of the placenta. The arithmetic mean of the volumes of glomeruli showed no statistically significant difference. In proximal tubules, all karyometric parameters of the treated group were significantly higher in relation to the control group (value p<0.01). Distal tubules showed an increase in the most karyometric parameters, with statistical significance in the treated group when compared to the control group, except for major/minor diameter ratio, eccentricity and contour index. There was no statistical significance when comparing both groups for the karyometric parameters of the cells of collecting tubules. Conclusions: Sucralose causes reduction of fetal weight and length of the umbilical cord. In fetal kidney, it causes significant changes in various nuclear parameters of cells of the proximal and distal convoluted tubule, suggesting transit of sucralose through the placental membrane and risks of nephrotoxicity.